# What is the value of n in the equation (n - 4) - 3 = 3 - (2n + 3)?

**Solution :**

Given: Equation is (n - 4) - 3 = 3 - (2n + 3)

Simplifying bracket terms

⇒ n - 4 - 3 = 3 - 2n -3

Separating n terms and constant terms

⇒ n + 2n = 3 - 3 + 4 +3

⇒ 3n = 7

⇒ n= 7/3.

## What is the value of n in the equation (n - 4) - 3 = 3 - (2n + 3)?

**Summary:**

The value of n in the equation (n - 4) - 3 = 3 - (2n + 3) is 7/3. An equation is like a weighing balance with equal weights on both sides. If we add or subtract the same number from both sides of an equation, it still holds.